Notes on typification of three names in Jurinea (Asteraceae) - Altinordu, Fahim; Crespo, Manuel B. (Phytotaxa, 2016)
The names of three species of Jurinea occurring in Turkey, Jurinea consanguinea, J. kilaea and J. mesopotamica, are typified. Lectotypes for J. kilaea and J. mesopotamica are designated from their original material conserved in the herbaria G and W, respectively. Furthermore, comments are given on the type material of J. consanguinea, with the location of the lectotype at G, and an isolectotype at K.